2007
DOI: 10.1159/000109747
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Mild Cognitive Impairment Is Highly Prevalent after Lacunar Stroke but Does Not Increase over Time: A 2-Year Follow-Up Study

Abstract: Although ample research has been done into cognitive disorders occurring after stroke, relatively few data are available on the development and the course of vascularmild cognitive impairment (VMCI) after first-ever lacunar stroke. Methods: A cohort of 95 patients with a first-ever symptomaticlacunar infarct, older than 40 years, MMSE ≧15 and no other neurological or major psychiatric deficits were included. Patients were assessed (clinically and with a neuropsychological test battery) at 1 and 24 months after… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
1

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 61 publications
0
23
0
1
Order By: Relevance
“…29 Other reports in MCI patients did not find an association between lacunes and progression to dementia. 9,31 In this study, Cox analysis of lacunes in the basal ganglia was, although borderline significant; suggestive of a Ͼ2-fold elevated risk of progression to a non-Alzheimer dementia. We did not find a predictive value of large-vessel infarcts on progression of MCI to dementia.…”
Section: Discussionmentioning
confidence: 51%
“…29 Other reports in MCI patients did not find an association between lacunes and progression to dementia. 9,31 In this study, Cox analysis of lacunes in the basal ganglia was, although borderline significant; suggestive of a Ͼ2-fold elevated risk of progression to a non-Alzheimer dementia. We did not find a predictive value of large-vessel infarcts on progression of MCI to dementia.…”
Section: Discussionmentioning
confidence: 51%
“…At follow-up, regardless of the severity of baseline impairment or time between assessments, all studies reported that stroke patients showed similar performance to baseline across domains, whether assessed by comparison to controls, 31,32,35 within-group, 33 or as a diagnostic classification. 34 Thus, data extraction revealed no consistent evidence that individuals with lacunar stroke show greater or different decline than controls over time.…”
Section: Imagingmentioning
confidence: 95%
“…12,13,15,[22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] Results showed high interrater reliability for article selection (Cohen k 5 0.78). Percent positive agreement was also excellent, with 83.3% agreement on article selection between the primary and independent raters.…”
Section: Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…37 It also is possible that the risk of cognitive decline or MCI in cognitively normal participants with infarcts will increase with longer follow-up and subsequent infarcts affecting cognition, as demonstrated previously. 7,38 Another reason, however, may be nonparticipation bias. Although all MCSA participants were offered MRI/MRS examinations, only 61% of the sample with a follow-up visit participated in the MRI/MRS study.…”
Section: Mrimentioning
confidence: 99%